QUALITY OF SERVICE DIPLOMA RECORDING SYSTEM USING SMART CONTRACTS AND NFT POLYGON NETWORK ON LAYER-2 ETHEREUM BLOCKCHAIN - Judhie Putra, Rizky Rachman; Nursalman, Muhamad; Kautsar, Fawwaz (Jurnal Teknik Informatika (Jutif), 2024)
A diploma is a document or certificate given to someone who has completed formal education. Diplomas are generally used as a benchmark for someone to get a job and identity in the eyes of the social environment. Many people think that a diploma is something meaningful or essential, so diplomas are often faked which violates legal norms and violates someone's Intellectual Property Rights (IPR). To anticipate counterfeiting, in Indonesia, there is currently a National Diploma Numbering (PIN) system and an Online Diploma Verification System (SIVIL), but unfortunately, the diploma database storage is still centralized which still allows illegal hacking to occur. On this basis, this research was created to able to provide a safer and more reliable diploma recording system solution, by utilizing Blockchain technology it is possible that every diploma issued can also be turned into a digital asset in the form of an NFT diploma, which is easy to track without having to face traditional bureaucratic obstacles. The NFT diploma functions as a representation of ownership, academic credentials, or identity as a sign of a student's educational history. This research aims to determine the performance of the Blockchain storage system on the Polygon network using smart contracts and IPFS. Apart from that, this research will compare the performance with previous research that used Polygon's layer-1, namely Ethereum. In smart contract cost testing, it was found that each Polygon transaction fee only requires 2.26% of the Ethereum transaction fee. Meanwhile, Quality of Service testing resulted in a throughput of 48.6-49.6 Kbps, packet loss of 0%, and latency of 42.07-44.13 m/s. The results show the potential for better cost efficiency and performance on the Polygon network compared to Ethereum.